An inflammatory and trophic disconnect biomarker profile revealed in Down syndrome plasma: Relation to cognitive decline and longitudinal evaluation. Issue 11 (21st July 2016) - Iulita, M. Florencia; Ower, Alison; Barone, Concetta; Pentz, Rowan; Gubert, Palma; Romano, Corrado; Cantarella, Rita Anna; Elia, Flaviana; Buono, Serafino; Recupero, Marilena; Romano, Carmelo; Castellano, Sabrina; et al.
Abstract: Introduction: Given that Alzheimer's pathology develops silently over decades in Down syndrome (DS), prognostic biomarkers of dementia are a major need. Methods: We investigated the plasma levels of Aβ, proNGF, tPA, neuroserpin, metallo‐proteases and inflammatory molecules in 31 individuals with DS (with and without dementia) and in 31 healthy controls. We examined associations between biomarkers and cognitive decline. Results: Aβ40 and Aβ42 were elevated in DS plasma compared to controls, even in DS individuals without dementia. Plasma Aβ correlated with the rate of cognitive decline across 2 years. ProNGF, MMP‐1, MMP‐3, MMP‐9 activity, TNF‐α, IL‐6, and IL‐10 were higher in DS plasma, even at AD‐asymptomatic stages. Declining plasma Aβ42 and increasing proNGF levels correlated with cognitive decline. A combined measure of Aβ and inflammatory molecules was a strong predictor of prospective cognitive deterioration. Conclusions: Our findings support the combination of plasma and cognitive assessments for the identification of DS individuals at risk of dementia.